Lifecycle of a Large-Scale Polar Coronal Pseudostreamer/Cavity System - Guennou, Chloé; Rachmeler, Laurel A.; Seaton, Daniel B.; Auchère, Frédéric (Frontiers in Astronomy and Space Sciences, 2016)
We report on an exceptional large-scale coronal pseudostreamer/cavity system in the southern polar region of the solar corona that was visible for approximately a year starting in February 2014. It is unusual to see such a large closed-field structure embedded within the open polar coronal hole. We investigate this structure to document its formation, evolution and eventually its shrinking process using data from both the PROBA2/SWAP and SDO/AIA EUV imagers. In particular, we used EUV tomography to find the overall shape and internal structure of the pseudostreamer and to determine its 3D temperature and density structure using DEM analysis. We found that the cavity temperature is extremely stable with time and is essentially at a similar or slightly hotter temperature than the surrounding pseudostreamer. Two regimes in cavity thermal properties were observed: during the first 5 months of observation, we found lower density depletion and highly multi-thermal plasma, while after the pseudostreamer became stable and slowly shrank, the depletion was more pronounced and the plasma was less multithermal. As the thermodynamic properties are strongly correlated with the magnetic structure, these results provide constraints on both the trigger of CMEs and the processes that maintain cavities stability for such a long lifetime.